Sosialisasi Praktek Jual Beli Kotoran Hewan Menurut Mazhab Imam Syafi’i - Suaib Lubis; Alang Sidek; Imanullah Imanullah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2021)
Based on the practice of the buying and selling system of animal dung in the village of Tanjung Putus, Padang Tualang sub-district, Langkat district, the sale of animal dung is a common thing among the community and is in accordance with the principles of sharia and the rules of buying and selling. Starting from the pillars of buying and selling conditions, goods and so on so that the sale and purchase of animal dung in Tanjung Putus village, Padang Tualang sub-district, Langkat district according to religion may be carried out and does not violate religious norms. 2. Based on Islamic Law's Istihsan Perspective on the sale and purchase of animal dung according to the goods which are unclean, it is prohibited by religion. In the development of customs that demand for manure as additional fertilizer for plantations and agriculture, the sale and purchase of animal dung is legally allowed, because there are benefits. Even though the Imams of Madhzab have different objects, there is animal dung to be used as manure, so it can be said that it is permissible for buying and selling transactions. Keywords: Buying and Selling, Dirt, Animals.